A mesoscale study of thermal expansion behaviors of epoxy resin and carbon fiber/epoxy unidirectional composites based on periodic temperature and displacement boundary conditions. (October 2016) - Dong, Kai; Zhang, Jiajin; Cao, Miao; Wang, Minglin; Gu, Bohong; Sun, Baozhong
Abstract: The thermal expansion behaviors of neat epoxy resin and carbon fiber/epoxy unidirectional (UD) composites were experimentally and numerically studied in this paper. The dynamic mechanical analysis (DMA), thermogravimetric analysis (TG), differential scanning calorimetry (DSC) and thermal conductivity measurement were used to measure the thermo-mechanical properties of epoxy resin at different temperatures. The dilatometer was used to measure the thermal strains and linear CTEs of neat epoxy resin and UD composites. In addition, a mesoscale finite element model based on the periodic temperature and displacement boundary conditions was presented to analyze the thermal expansion behaviors of UD composites. The resin-voids representative volume element (RVE) was used to calculate the thermo-mechanical properties of several kinds of resin-voids mixed matrix. From the results it can be found that the glass transition temperature of epoxy resin, porosity and fiber orientation angle have significant effects on the thermal expansion behaviors of UD composites. The mesoscale finite element analyses (FEA) have obvious advantages than various existing analysis models by comparing their predictive results. The distributions of thermal displacement, thermal stress and thermal strain were extracted between the carbon fiber, resin-voids mixed matrix and their interface, and also between the front and back surfaces of the loading direction, to further investigate thermal expansion structure effects of UD composites. This paper revealed that the mesoscale FEA based on periodic temperature and displacement boundary conditions can be also used for thermal expansion researches of other complex structure composites.